Réponses

Meilleure réponse !
2012-05-15T01:06:19+02:00

Bonsoir Titodu51,

Voici ce que j'ai trouvé :

 

a)                                               2x + 3 = 3x - 5

                                                 2x - 3x = -5 - 3

                                                        -x = -8

                                                         x = 8 

 

b)                                           2 (x + 3) = 3x - 5

                                          2 * x + 2 * 3 = 3x - 5

                                                  2x + 6 = 3x - 5

                                                 2x - 3x = -5 - 6 

                                                        -x = -11

                                                         x = 11

 

c)                                               2x + 3 = 3 (x - 5)

                                                  2x + 3 = 3 * x - 3 * 5

                                                 2x - 3x = -15 - 3

                                                         -x = -18

                                                          x = 18

 

En espérant t'avoir aidé, 

Mistouille